Fabrication of Lead Borate Single Crystal Nanosheets for Attenuating Both Neutron and Gamma Radiations1 . Issue 3 (29th December 2016) - Zhang, Quan‐Ping; Sun, Nan; Zheng, Jian; Wang, Shi‐Wei; Wu, You; Luo, De‐Li; Zhou, Yuan‐Lin
Abstract : In this work, Pb3 B10 O16 [OH]4 single crystal nanosheets are fabricated by a solvothermal process. Its structure is determined in detail by XRD, SEM, and TEM. The nanosheets display a good ability to attenuate both neutron and gamma radiations. In particular, it provides a distinct advantage to attenuate the gamma radiation with low energy from 59 to 105 keV. Notably, the lead borate single crystals with 2D nanostructures impliy other benefits, such as mechanical enhancement and high thermal conductivity. Thus, the lead borate nanosheets can be applied to the fabrication of multifunctional integrated composites for the radiation protection of complex conditions. Abstract : Lead borate single crystal nanosheets have been fabricated by a facile solvothermal process. The 2D nanostructure exhibits an excellent ability to attenuate both neutron and gamma radiations. Importantly, the lead borate exhibits 2D nanostructures that imply other amazing physical properties, such as mechanical enhancement, high thermal conductivity. Thus, the product can be applied to the fabrication of multifunction integrated composites for the radiation protection of complex conditions.